THE OPUS STUDY: OSTEOPOROSIS PREVENTION USING SOY - Aydogan, C.; Wong, W.; Lewis, R.; Steinberg, F.; Margaret, M. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
A study was designed to (1) evaluate the effect of soy isoflavones on bone loss as well as to (2) determine the long-term safety of extracted isoflavones in a tablet form. Design: 403 Early postmenopausal women (54.01Â±3.97 y) were enrolled in an intent-to-treat, multi-site, 2-year follow-up, randomized, double-blind study with 1/3 on placebo, 1/3 on 80 mg/d of isoflavones, and 1/3 on 120 mg/d of isoflavones (SoyLife EXTRA, soy germ isoflavones) along with 1,000 mg/d of CaCO3 and a daily multivitamin with 400 IU of vitamin D. Bone mineral content (BMC), bone mineral density (BMD), and serum levels of biochemical bone markers were measured at baseline and annual intervals. The safety indicators included serum electrolytes, lipids, liver and renal functions, complete blood counts, reproductive and thyroid hormones and cancer screening. Results: Baseline characteristics were similar in the three groups. A statistically significant, but small effect on the decrease in whole body BMD was observed with soy isoflavone intake at 120 mg/d vs. placebo after 1 y (p=0.027) and 2 y (p=0.048) of supplementation. Changes in biochemical safety indicators were neither outside the normal range nor clinically significant. Major adverse effects included one subject with endometrial cancer and one with breast cancer, which were fewer than predicted in this study population. Conclusion: Soy isoflavone supplementation (120 mg/d) appears to be safe and may modestly prevent early menopausal loss of whole body BMD. The benefit was not observed in regional sites with high trabecular bone content.